Excess of heme induces tissue factor-dependent activation of coagulation in mice - Erica M. Sparkenbaugh; Pichika Chantrathammachart; Shaobin Wang; Will Jonas; Daniel Kirchhofer; David Gailani; Andras Gruber; Raj Kasthuri; Nigel S. Key; Nigel Mackman; Rafal Pawlinski (Haematologica, 2015)
An excess of free heme is present in the blood during many types of hemolytic anemia. This has been linked to organ damage caused by heme-mediated oxidative stress and vascular inflammation. We investigated the mechanism of heme-induced coagulation activation in vivo. Heme caused coagulation activation in wild-type mice that was attenuated by an anti-tissue factor antibody and in mice expressing low levels of tissue factor. In contrast, neither factor XI deletion nor inhibition of factor XIIa-mediated factor XI activation reduced heme-induced coagulation activation, suggesting that the intrinsic coagulation pathway is not involved. We investigated the source of tissue factor in heme-induced coagulation activation. Heme increased the procoagulant activity of mouse macrophages and human PBMCs. Tissue factor-positive staining was observed on leukocytes isolated from the blood of heme-treated mice but not on endothelial cells in the lungs. Furthermore, heme increased vascular permeability in the mouse lungs, kidney and heart. Deletion of tissue factor from either myeloid cells, hematopoietic or endothelial cells, or inhibition of tissue factor expressed by non-hematopoietic cells did not reduce heme-induced coagulation activation. However, heme-induced activation of coagulation was abolished when both non-hematopoietic and hematopoietic cell tissue factor was inhibited. Finally, we demonstrated that coagulation activation was partially attenuated in sickle cell mice treated with recombinant hemopexin to neutralize free heme. Our results indicate that heme promotes tissue factor-dependent coagulation activation and induces tissue factor expression on leukocytes in vivo. We also demonstrated that free heme may contribute to thrombin generation in a mouse model of sickle cell disease.